Tough oxidized chitosan hybrid gelatin hydrogel with high photothermal conversion performance and preparation thereof
Through the composite of oxidized chitosan and gelatin, hybrid hydrogels with high photothermal conversion performance are formed, which solves the problems of insufficient mechanical properties and environmental friendliness of traditional hydrogels, and achieves high-efficiency photothermal conversion and self-healing performance. Suitable for a variety of application scenarios, significantly improving mechanical properties and durability.
Patent Information
- Application Number
- CN202411457164.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Traditional photothermal hydrogels have problems such as insufficient mechanical properties, poor durability, limited functionality, high cost and risk of toxicity and environmental pollution, which limit their use in applications requiring efficient photothermal conversion, low cost and environmentally friendly.
Hybrid hydrogels with high photothermal conversion performance are prepared by combining oxidized chitosan and gelatin. By combining oxidized chitosan and gelatin, hybrids with high intensity, high photothermal conversion efficiency and good biocompatibility are formed. Hydrogel materials use hydrogen bonding and electrostatic action of oxidized chitosan and gelatin to form an enhanced crosslinking structure, achieving more than 98% full-spectrum solar energy absorption and photothermal-driven self-healing performance.
Achieve high-efficiency photothermal conversion performance, significantly improve tensile strength and toughness, maintaining 92% photothermal drive self-healing efficiency, suitable for photothermal therapy, wound healing, temperature control sensors and solar energy capture, and has excellent mechanical properties and antibacterial properties significantly surpass the durability and reliability of traditional hydrogels.
Smart Images

Figure CN119264679A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a strong and tough oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance and a preparation method thereof. Background Art
[0002] In recent years, hydrogels have gained wide attention in many fields such as biomedicine, flexible electronics, environmental management and energy conversion due to their unique three-dimensional network structure, adjustable mechanical properties and good biocompatibility. Hydrogels can absorb a large amount of water while maintaining the stability of their own structure, so they show great potential in applications such as flexible sensors, tissue engineering, drug release and wound healing. However, traditional hydrogels have problems such as insufficient mechanical properties, poor durability and limited functionality, which limit their application in environments that require higher strength and durability.
[0003] Photothermal conversion hydrogel is an emerging type of material. By embedding photothermal conversion substances (such as carbon-based materials, metal nanoparticles or organic dyes, etc.) into the hydrogel matrix, it can efficiently convert light energy into thermal energy after absorbing it. This type of material has broad application prospects in solar energy capture, photocatalytic sterilization, temperature-controlled release and intelligent response. However, the photothermal materials commonly used in traditional photothermal hydrogels are expensive and have risks of toxicity and environmental pollution. Therefore, the development of hydrogel materials with high-efficiency photothermal conversion performance, low cost, environmental friendliness, and excellent mechanical properties has become a technical problem that needs to be solved urgently.
[0004] In this context, natural polymer materials have gradually attracted attention as a low-cost, sustainable and environmentally friendly photothermal conversion material. Chitosan is a natural polysaccharide widely found in the exoskeleton of crustaceans, with good biocompatibility, degradability and chemical modification ability. On the other hand, gelatin is a natural protein polymer extracted from animal collagen, with good biocompatibility, degradability and processability, and is widely used in the preparation of hydrogels.
[0005] At present, although some hydrogels have been applied in the field of photothermal conversion, most of them face problems such as insufficient photothermal conversion efficiency, poor mechanical properties and lack of antibacterial properties. Therefore, the development of hydrogels with high photothermal conversion efficiency and excellent mechanical properties will provide new application prospects and technical solutions for biomedicine, energy conversion and environmental governance. Summary of the invention
[0006] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a strong oxidized chitosan hybrid gelatin hydrogel with high photothermal conversion performance.
[0007] The present invention prepares hydrogel by compounding oxidized chitosan and gelatin, fully combining the advantages of both, and forming a hybrid hydrogel material with high strength, high photothermal conversion efficiency and good biocompatibility. The photothermal conversion efficiency of the oxidized chitosan / gelatin hybrid hydrogel of the present invention is significantly improved, making it show great potential in photothermal therapy, wound healing, temperature control sensors and solar energy capture applications.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned oxidized chitosan hybrid gelatin hydrogel.
[0009] Another object of the present invention is to provide applications of the above-mentioned oxidized chitosan hybrid gelatin hydrogel, especially in the fields of photothermal therapy, wound healing, temperature control sensors and solar energy capture.
[0010] The purpose of the present invention is achieved through the following solutions:
[0011] A strong oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance comprises the following components in parts by weight: 80-100 parts of water, 20-40 parts of gelatin, 1-5 parts of oxidized chitosan, and 0.5-2 parts of soluble metal salt.
[0012] Furthermore, the gelatin can be any gelatin commonly used in the art, and may include at least one of fish skin gelatin and chicken skin gelatin.
[0013] Furthermore, the carboxyl content of the oxidized chitosan may be 5-30%, more preferably 10-25%.
[0014] Furthermore, the oxidized chitosan can be chitosan obtained by oxidation treatment known in the art, such as at least one of hydrogen peroxide / divalent metal ion oxidized chitosan, potassium permanganate oxidized chitosan, and TEMPO oxidized chitosan, preferably hydrogen peroxide / divalent metal ion oxidized chitosan.
[0015] Furthermore, the soluble metal salt includes at least one of potassium citrate, sodium citrate, calcium citrate and the like.
[0016] The hydrogel of the present invention is obtained by compounding oxidized chitosan and gelatin, which fully combines the advantages of both. Oxidized chitosan is rich in amino and carboxyl groups, and forms a strong hydrogen bond and electrostatic force with gelatin hydroxyl / amino groups, promoting the formation of gelatin crystal domains and producing strong physical crosslinks, forming a hybrid hydrogel material with high strength, high photothermal conversion efficiency and good biocompatibility, which can achieve more than 98% full-spectrum solar energy absorption. And the hydrogel of the present invention has photothermal driven self-healing properties, and after five damage / self-healing cycles, it can still maintain 92% photothermal driven self-healing efficiency.
[0017] The present invention also provides a method for preparing the above-mentioned oxidized chitosan hybrid gelatin hydrogel, comprising the following steps: uniformly mixing the components in proportion, heating and dissolving them, and preparing the oxidized chitosan hybrid gelatin hydrogel after low-temperature gelation.
[0018] Furthermore, the temperature may be raised to 60-100° C., and the dissolution time may be 0.5-5 h.
[0019] Furthermore, the low temperature may be 5-15° C., and the gelation time may be 12-48 h.
[0020] The oxidized chitosan hybrid gelatin hydrogel in the present invention has excellent mechanical properties and photothermal self-healing properties through the photothermal conversion ability and macromolecular cross-linking characteristics of the special structure formed by gelatin and oxidized chitosan, thereby overcoming the shortcomings of traditional hydrogel materials; the oxidized chitosan hybrid gelatin hydrogel in the present invention also has excellent antibacterial and water-retention properties, and is suitable for a variety of application scenarios, such as flexible sensors, photothermal therapy, photothermal power generation, energy storage and other fields.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The oxidized chitosan hybrid gelatin hydrogel of the present invention has excellent mechanical properties, and its tensile strength and toughness reach 5.53MPa and 9.81MJ·m -3 .
[0023] (2) The oxidized chitosan hybrid gelatin hydrogel based on the present invention has high photothermal conversion performance, achieving more than 98% full-spectrum solar energy absorption, and can still maintain 92% photothermal-driven self-healing efficiency after five damage / self-healing cycles.
[0024] (3) The oxidized chitosan in the oxidized chitosan hybrid gelatin hydrogel of the present invention, as a molecularly dispersed macromolecular crosslinking agent, can form abundant crosslinking points between gelatin molecular chains through electrostatic interaction and hydrogen bonding, promoting the aggregation of gelatin chains into more triple helical structures. These crosslinking points and crystallized regions act as energy dissipation points to prevent the macromolecular chains from sliding rapidly when subjected to force, thereby simultaneously strengthening and toughening the hydrogel.
[0025] (4) The oxidized chitosan hybrid gelatin hydrogel of the present invention effectively absorbs solar energy and converts it into heat when exposed to sunlight. This heat generation exists at the molecular level due to the strong intermolecular interactions between water-soluble oxidized chitosan and gelatin chains in the hydrogel matrix. When the absorbed light energy is converted into heat, the temperature within the hydrogel increases, resulting in a local warming effect. The increase in temperature triggers the gel-sol transition in the organic hydrogel, causing the gelatin matrix to temporarily soften. In this softened state, the molecular network can be quickly reorganized to effectively heal cracks or damage, so that the oxidized chitosan hybrid gelatin hydrogel of the present invention exhibits excellent photothermal-driven self-healing properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 The mechanical properties of the oxidized chitosan hybrid gelatin hydrogel of the present invention.
[0028] Figure 2 This is the self-healing process of the oxidized chitosan hybrid gelatin hydrogel of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified. The amount of each component is measured by mass volume, g, mL.
[0030] The gelatin (chemically pure) used in the following examples was purchased from Sinopharm Chemical Reagent Co., Ltd.; chitosan and metal salts such as potassium citrate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0031] The oxidized chitosan used in the present invention can be purchased, including at least one of hydrogen peroxide / divalent metal ion oxidized chitosan, potassium permanganate oxidized chitosan, and TEMPO oxidized chitosan. For better comparison, the following examples all use hydrogen peroxide / divalent metal ion oxidized chitosan, which can be prepared by the following steps: after dispersing chitosan in water, adding a certain amount of 30wt.% hydrogen peroxide solution and anhydrous copper sulfate catalyst, and continuing the reaction for 48 hours with mechanical stirring at 600rpm. After the reaction is completed, the obtained product is repeatedly centrifuged and washed until the washing liquid is neutral, and freeze-dried to constant weight to obtain oxidized chitosan. By controlling the amount of hydrogen peroxide and copper sulfate used, oxidized chitosan with different carboxyl contents can be prepared. The following examples all use oxidized chitosan with a carboxyl content of 20%.
[0032] Example 1
[0033] 30 parts by mass of gelatin, 1 part by mass of oxidized chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0034] Example 2
[0035] 30 parts by mass of gelatin, 2 parts by mass of oxidized chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0036] Example 3
[0037] 30 parts by mass of gelatin, 3 parts by mass of oxidized chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0038] Example 4
[0039] 30 parts by mass of gelatin, 4 parts by mass of oxidized chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0040] Example 5
[0041] 30 parts by mass of gelatin, 5 parts by mass of oxidized chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0042] Example 6
[0043] 30 parts by mass of gelatin, 5 parts by mass of oxidized chitosan, and 1 part by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0044] Example 7
[0045] 30 parts by mass of gelatin, 5 parts by mass of oxidized chitosan, and 2 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0046] Example 8
[0047] 30 parts by mass of gelatin, 5 parts by mass of oxidized chitosan, and 1.5 parts by mass of sodium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0048] Example 9
[0049] 30 parts by mass of gelatin, 5 parts by mass of oxidized chitosan, and 1.5 parts by mass of calcium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain an oxidized chitosan hybrid gelatin hydrogel.
[0050] Comparative Example 1
[0051] 30 parts by mass of gelatin and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the mixture was stirred continuously for 5 minutes under a vacuum environment to remove bubbles. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain a gelatin hydrogel.
[0052] Comparative Example 2
[0053] 30 parts by mass of gelatin, 5 parts by mass of ordinary chitosan, and 1.5 parts by mass of potassium citrate were added to 100 parts by mass of deionized water and mixed evenly. The mixture was mechanically stirred at 80°C for 1 hour to form a uniform viscous solution. A flask equipped with a spherical condenser tube was sealed with silicone grease to prevent water vapor diffusion at high temperature. Then, the bubbles were removed by continuous stirring for 5 minutes under a vacuum environment. Subsequently, the mixed solution was transferred to a rectangular polytetrafluoroethylene mold with a thickness of 3 mm, and then gelled at 5°C for 1 hour to obtain a chitosan hybrid gelatin hydrogel.
[0054] The hydrogels prepared in Examples 1-9 and Comparative Examples 1-2 were subjected to tensile strength tests (tested according to ASTM D638-2003 standard, with a tensile rate of 50 mm / min); photothermal conversion performance tests (light intensity of 100 mW / cm 2 ), the test results are shown in Table 1 and Figure 1 shown.
[0055] From Table 1 and Figure 1 It can be seen that the tensile strength and toughness of the oxidized chitosan hybrid gelatin hydrogel of the present invention are significantly improved compared with pure gelatin hydrogel and original chitosan hybrid gelatin hydrogel. The introduction of oxidized chitosan significantly enhances the intermolecular interaction of the hydrogel, and constructs a tough three-dimensional network structure by forming multiple hydrogen bonds and electrostatic interactions. Oxidized chitosan can be used as a macromolecular cross-linking agent dispersed at the molecular level, forming abundant cross-linking points between gelatin molecular chains through electrostatic interactions and hydrogen bonds, and promoting the aggregation of gelatin chains into more triple helical structures. These cross-linking points and crystallization regions act as energy dissipation points to prevent the macromolecular chains from slipping rapidly when subjected to force, thereby simultaneously strengthening and toughening the hydrogel. Oxidized chitosan / gelatin hybrid hydrogel combines the advantages of oxidized chitosan and gelatin, showing significantly enhanced mechanical properties. The addition of metal salts such as potassium citrate further enhances the cross-linking strength and molecular chain entanglement through the Hoffman effect. Through the Hoffman effect, the convergence and crystallization of gelatin and oxidized chitosan molecular chains are strengthened. This structure not only provides higher strength and toughness, but also enables the hydrogel to exhibit better ductility and fatigue resistance under stress.
[0056] Table 1
[0057]
[0058] Self-healing performance test operation: a deep crack was made in the middle of the dumbbell-shaped specimen, and the damaged part was exposed to 100mW / cm 2 After different self-healing cycles, the mechanical properties of the samples were tested and the self-healing process was observed using an optical microscope. Figure 2 , Figure 2 These are the photothermal self-healing images of the hydrogel in Example 3 taken under a microscope at 0, 2, 3, and 6 minutes respectively.
[0059] As can be seen from the figure, the hydrogel of the present invention shows self-repairing ability, which realizes rapid self-repair driven by photothermal conversion during the photothermal conversion process. The oxidized chitosan hybrid gelatin hydrogel of the present invention has a significantly enhanced light absorption capacity, and further releases heat energy through intramolecular chemical bond vibration, making it an effective photothermal converter. When exposed to sunlight, it can effectively absorb solar energy and convert it into heat. Due to the strong intermolecular interactions between water-soluble oxidized chitosan and gelatin chains in the hydrogel, this heat generation exists at the molecular level. These interactions occur at sub-nanometer spacings. When the absorbed light energy is converted into heat, the temperature in the hydrogel increases, resulting in a local warming effect. The increase in temperature triggers the gel-sol transition in the organic hydrogel, temporarily softening the gelatin matrix. In this softened state, the molecular network can be quickly reorganized to effectively heal cracks or damage. This self-healing property is particularly suitable for application scenarios that require long-term reliability, such as solar-driven devices, smart sensors, and medical devices. Therefore, the oxidized chitosan hybrid gelatin hydrogel of the present invention not only has efficient photothermal conversion performance, but also significantly surpasses traditional hydrogels in mechanical properties, providing a solution with excellent reliability and durability.
[0060] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A strong oxidized chitosan hybrid gelatin hydrogel with high photothermal conversion performance, characterized in that The invention comprises the following components in parts by weight: 80-100 parts of water, 20-40 parts of gelatin, 1-5 parts of oxidized chitosan and 0.5-2 parts of soluble metal salt.
2. The strong oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance according to claim 1, characterized in that: The carboxyl content of the oxidized chitosan is 5-30%.
3. The strong and tough oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance according to claim 1, characterized in that: The carboxyl content of the oxidized chitosan is 10-25%.
4. The strong oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance according to claim 1, characterized in that: The oxidized chitosan includes at least one of hydrogen peroxide / divalent metal ion oxidized chitosan, potassium permanganate oxidized chitosan and TEMPO oxidized chitosan.
5. The strong and tough oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance according to claim 1, characterized in that: The oxidized chitosan comprises chitosan oxidized by an improved Fenton reagent.
6. The strong and tough oxidized chitosan hybrid gelatin hydrogel with high light-to-heat conversion performance according to claim 1, characterized in that: The soluble metal salt includes at least one of potassium citrate, sodium citrate and calcium citrate.
7. A method for preparing a tough oxidized chitosan hybrid gelatin hydrogel with high photothermal conversion performance as described in any one of claims 1 to 6, characterized in that The method comprises the following steps: uniformly mixing the components in proportion, heating and dissolving the components, and gelling the components at low temperature to prepare the oxidized chitosan hybrid gelatin hydrogel.
8. The preparation method according to claim 7, characterized in that: The heating refers to heating to 60-100° C., and the dissolving time is 0.5-5 hours.
9. The preparation method according to claim 7, characterized in that: The low temperature is 5-15°C and the gelation time is 12-48h.
10. Application of the tough oxidized chitosan hybrid gelatin hydrogel with high photothermal conversion performance as described in any one of claims 1 to 6 in the fields of flexible sensors, photothermal therapy, photothermal power generation, and energy storage.
Citation Information
Patent Citations
Self-formed tubular or cup-shaped high-strength hydrogel and preparation method thereof
CN106496601A
Chitosan-based biological tissue adhesive as well as preparation method and application thereof
CN114470306A
Preparation method of wound dressing based on shaddock peel pectin-oxidized chitosan composite hydrogel
CN114712553A
Self-adhesion intrinsic ion conductive hydrogel as well as preparation method and application thereof
CN118620131A
KR20240052147A